Bray-Curtis Distance Untuk Pencarian Resep Kue Tradisional Berdasarkan Ketersediaan Bahan Makanan - Febriana Ranta Lidya; Yuita Arum Sari; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In modern times like today there are several problems, especially regarding the introduction of traditional food which is one of the cultural heritages. Most Indonesian people today prefer modern cuisine to traditional food, especially for general snacks such as cakes. The lack of introduction of traditional cakes to the community is currently the background of a bray-curtis distance study to search for traditional cake recipes based on the availability of food ingredients. In this study the data used are food recipes obtained from Twitter users using the number of likes and retweets and are processed using the Bray-Curtis Distance calculation, and also compare with Euclidean Distance, the influence of Like and Retweet are also seen to find out whether the likes and retweets can provide better traditional cake search results. The Bray-Curtis Distance and Euclidean Distance Calculation Results for MAP produce the MAP value for Bray-Curtis Distance on Top-1 is 0.76 while for Euclidean Distance on Top-1 gives 0.18 results. In this case it can be seen that Bray-Curtis Distance is superior compared to Euclidean Distance, this is because in Euclidean Distance occurs in words that have high dimensions so it cannot work properly, because Euclidean Distance will assume that there is a high degree of dependency between vectors coordinates on the vector.